A Mechanosensitive Channel Governs Lipid Flippase-Mediated Echinocandin Resistance in Cryptococcus neoformans - Cao, Chengjun (mBio, 2019)
Echinocandins show fungicidal activity against common invasive mycoses but are ineffective against cryptococcosis. The underlying mechanism for echinocandin resistance in Cryptococcus neoformans remains poorly understood but has been shown to involve Cdc50, the regulatory subunit of lipid flippase. In a forward genetic screen for cdc50Δ suppressor mutations that are caspofungin resistant, we identified Crm1 (caspofungin resistant mutation 1), a homolog of mechanosensitive channel proteins, and showed that crm1Δ restored caspofungin resistance in cdc50Δ cells. Caspofungin-treated cdc50Δ cells exhibited abnormally high intracellular calcium levels ([Ca(2+)]c) and heightened activation of the calcineurin pathway. Deletion of CRM1 in the cdc50Δ background normalized the abnormally high [Ca(2+)]c. Cdc50 interacts with Crm1 to maintain cellular calcium homeostasis. Analysis of chitin/chitosan content showed that deleting CRM1 reversed the decreased chitosan production of cdc50Δ cells. Together, these results demonstrate that Cdc50 and Crm1 regulation of the calcineurin pathway and cytoplasmic calcium homeostasis may underlie caspofungin resistance in C. neoformans.